SELECTIVE PROCESS APLIED TO SPORTIVE MODALITIES AT BRAZIL (Fiep Bulletin - online, 2013)
Introduction: The youth selection methods with the purpose of composing teams in different sports are considered by many as fundamental. The aim of this study was to investigate the ones applied on the athlete's selection for the bases' categories from different sports at Brazil. Methodology: The method of this research was to review having as support the databases and specialized literature and confederations/federations' sites. Results: The analyzed documents pointed out that the selection process over the years has been discussed generating major discussion due to conflict between several ways as how has been conducted. The discussions are for the design of the sport performance depends on the effectiveness of income requirements and it's compliance with the levels of development of physical qualities, which are a result of complex processes of growth, development and maturation. It turns out, though, that the individual and collective modes, decumulated, do not diverge in this sense and that according to most authors, and athletes submitted are not in phase of development most appropriate for the acquisition of the basic skills necessary for most sports. Final considerations: Due to lack of scientific criteria guided the selection process of young people and the application of empirical procedures conducted inappropriately to age and fitness level, receptivity to exploration and development of their physical abilities, skills, motor coordination and with less potential for learning specific gestures. Failing to observe the formation of the individual and of the athlete continuously is still way over time to seek the early yield. Within this perspective is important for the resumption of the debate on the process of selecting athletes.
Keywords: Selection; basis' category athletes; sports